Classifying Inmates for Strategic Programming - Eileen Sullivan, Carmen Cirincione, Katherine Nelson, and Jennifer Wallis (My University, 2016)
In an effort to improve its methods of selecting jail inmates appropriate for drug treatment, the New York City Department of Corrections (DOC) asked Vera to design and test models that could predict length of stay. This presents the result of that work.